Structural, chemical, and mechanical properties of concrete developed from a binder composite of sugarcane bagasse ash and Portland cement - Michael Evans Nzugua; Emma Panzi Mukhokosi; Sam Obwoya Kinyera (Discover Materials)
Abstract The East Africa Community (EAC) countries have immense sugarcane cane bagasse ash (SCBA) which remains unexploited as a supplementary-cementitious material (SCM). This study delved into using EAC SCBA as a pozzolan. SCBA investigated was collected from Kenya’s coastal area. Raw SCBA, processed SCBA, Portland cement (PC) and the developed concrete were characterised by various techniques to determine the surface morphology, chemical composition, structural properties and mineralogical composition. The raw SCBA was calcined at 600 °C then used to design the concrete mix. PC was replaced with SCBA from 0 to 30% in steps of 10%. The flexural and compressive strengths were determined in the hardened state after 28 days of concrete curing. The compressive and flexural strengths of the mix containing 20% SCBA were higher than the control mix by 9.65 and 6.51%, respectively. The microstructural properties of the developed concrete revealed dense particle distribution, indicating good micro/nanofiller effects of the interfacial transition zone (ITZ). The processed SCBA was found to meet class N and F of natural pozzolan as per ASTM C 618. This study suggests that the Kenya coastal SCBA can be used as a supplementary cementitious material.